ECOSISTENCE OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN THE PERSPECTIVE OF INDONESIAN ECONOMIC POLICY IN INDONESIA - Rosmiati (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
In 1992, the Indonesian government launched the Village Unit Cooperative (KUD) initiative to develop rural economies through Law Number 25 of 1992 on Cooperatives. However, KUD faced various challenges that hindered its ability to achieve its goal of improving rural community welfare. Regulatory changes beginning with Law Number 22 of 1999 on Regional Government, followed by Law 32/2004, Law 23/2014, and Law 6/2014 on Villages, led to the establishment of Village-Owned Enterprises (BUMDes) as a new solution for rural economic development. This article explores the policy transformation from KUD to BUMDes and analyzes the effectiveness of the Job Creation Law and Government Regulation on BUMDes in strengthening BUMDes as a tool for village empowerment. The research methodology employed is a literature review encompassing legal documents, books, and scholarly articles. The findings reveal that the Job Creation Law and Government Regulation on BUMDes provide a more solid legal foundation for BUMDes by clarifying its legal status, defining its capital structure, and granting the authority to establish business units. The article also discusses relevant economic theories such as institutional theory, inclusive economic theory, and community-based development theory, as well as challenges and solutions in BUMDes development. Recommendations for BUMDes development include strengthening managerial capacity, improving access to capital, and devising business development strategies that focus on operational efficiency and community participation. The study concludes that BUMDes has significant potential to support local economic development and rural community welfare through more effective and participatory policies.